Lactate drives cellular DNA repair capacity: Role of lactate and related short-chain fatty acids in cervical cancer chemoresistance and viral infection - Ciszewski, Wojciech M.; Sobierajska, Katarzyna; Stasiak, Anna; Wagner, Waldemar (Frontiers in Cell and Developmental Biology, 2022)
The characteristic feature of a cancer microenvironment is the presence of a highly elevated concentration of L-lactate in the tumor niche. The lactate-rich environment is also maintained by commensal mucosal microbiota, which has immense potential for affecting cancer cells through its receptoric and epigenetic modes of action. Some of these lactate activities might be associated with the failure of anticancer therapy as a consequence of the drug resistance acquired by cancer cells. Upregulation of cellular DNA repair capacity and enhanced drug efflux are the most important cellular mechanisms that account for ineffective radiotherapy and drug-based therapies. Here, we present the recent scientific knowledge on the role of the HCA1 receptor for lactate and lactate intrinsic activity as an HDAC inhibitor in the development of an anticancer therapy-resistant tumor phenotype, with special focus on cervical cancer cells. In addition, a recent study highlighted the viable role of interactions between mammalian cells and microorganisms in the female reproductive tract and demonstrated an interesting mechanism regulating the efficacy of retroviral transduction through lactate-driven modulation of DNA-PKcs cellular localization. To date, very few studies have focused on the mechanisms of lactate-driven enhancement of DNA repair and upregulation of particular multidrug-resistance proteins in cancer cells with respect to their intracellular regulatory mechanisms triggered by lactate. This review presents the main achievements in the field of lactate impact on cell biology that may promote undesirable alterations in cancer physiology and mitigate retroviral infections.